2019
DOI: 10.34117/bjdv5n7-036
|View full text |Cite
|
Sign up to set email alerts
|

Increasing energy efficiency in microencapsulation of soybean oil by spray drying

Abstract: The aim of this study was to evaluate the influence of inlet air temperature of spray drying on microparticles properties and heat loss on drying chamber in sense to select the conditions that promote the preservation of functional compounds and improve energy efficiency. The energy efficiency of the process was evaluated varying inlet air temperature (T) from 110 to 150 °C and airflow (AF) from 20 to 40kg/h, being the energy efficiency, the response variable. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The emulsion was homogenized in a blender for 2 min. These operational conditions were adapted from James et al [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The emulsion was homogenized in a blender for 2 min. These operational conditions were adapted from James et al [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…An alternative to mitigate these limitations would be the encapsulation process, which aims to protect sensitive particles by isolating them from the external environment (Cano-Chauca, Stringheta, Ramos, & Cal-Vidal, 2005;Gharsallaoui, Roudaut, Chambin, Voilley, & Saurel, 2007). Many studies reported application of encapsulation (Di Giorgio, Salgado, & Mauri, 2019;Fadini et al, 2019;Silva James, Castro, Freitas, & Nogueira, 2019;Souza, Rocha, Brito, Galvão, & Nunes, 2019).…”
Section: Introductionmentioning
confidence: 99%